Trigonometry : A Right Triangle Approach - Sullivan, Michael; Michael Sullivan III (New Jersey : Pearson Education Asia Pte. Ltd., 2009)
Rather than provide a list of new features here, that information can be found on the end papers in the front of this book. This places the new features in their proper context, as a building blocks of ab overall learning system that has been carefully crafted over the years to help the student get the most out of the time they put into studying .
Part 1. Graphs and Function -- Part 2. Trigonometric Functions -- Part 3. Analytic Trigonometry -- Part 4. Applications of Trigonometric Functions -- Part 5. Polar Coordinates; Vectors -- Part 6. Analytic Geometry -- Part 7. Exponential and Logarithmic Functions .
Includes index.
Keywords: TRIGONOMETRY